2019
DOI: 10.33545/pathol.2019.v2.i1e.49
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of Salivary gland lesions

Abstract: Introduction: There is a wide spectrum of salivary gland lesions with morphologically and clinically diversity which is a difficult task for histopathological interpretation. There are three major salivary glands-parotid, submandibular, and sublingual as well as minor salivary glands distributed throughout the mucosa of the oral cavity. Neoplastic and non-neoplastic disease may develop within any of these. Aims: (1) To study the histopathological features of salivary gland lesions, (2) To study the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Out of 50 Muco-epidermoid carcinoma , present study reported (33 cases, 66%) of low grade Muco-epidermoid carcinoma which is consistent with a recent study in USA by Shafique et al 23 classified majority of mucoepidermoid carcinoma as low grade(44 cases, 64%) out of 69 cases. Acinic cell carcinoma presented as the third most common malignancy in present study, a finding similar to Chavda et al 24 and Huang et al 25 . However, Arrangoiz et al 26 mentioned acinic cell carcinoma as the second most common malignancy in parotid gland.…”
Section: Discussionsupporting
confidence: 92%
“…Out of 50 Muco-epidermoid carcinoma , present study reported (33 cases, 66%) of low grade Muco-epidermoid carcinoma which is consistent with a recent study in USA by Shafique et al 23 classified majority of mucoepidermoid carcinoma as low grade(44 cases, 64%) out of 69 cases. Acinic cell carcinoma presented as the third most common malignancy in present study, a finding similar to Chavda et al 24 and Huang et al 25 . However, Arrangoiz et al 26 mentioned acinic cell carcinoma as the second most common malignancy in parotid gland.…”
Section: Discussionsupporting
confidence: 92%